Effects of drying and simulated flooding on soil phosphorus dynamics from two contrasting UK grassland soils - Khan, Sidra U.; Hooda, Peter S.; Blackwell, Martin S. A.; Busquets, Rosa (European journal of soil science, 2022)
Flooding is known to mobilise soil phosphorus (P). However, it is still not clear how climate change‐driven extended periods of soil drying followed by flooding will affect soil‐P dynamics. We tested the hypothesis under laboratory conditions that soil antecedent conditions (moist/dry) determine the amount of P mobilised upon flooding. A series of controlled laboratory experiments were carried out by flooding samples of two contrasting soils (a Dystric Cambisol [Crediton series] and a Stagni‐Vertic Cambisol [Hallsworth series]), which had each been either dried (40°C for 10 days) or kept at field moisture conditions (25% moisture content). Flooding was simulated by maintaining a 10‐cm water column depth in mesocosms. Periodically collected water samples were analysed for dissolved reactive P (DRP), total dissolved P (TDP) and dissolved unreactive P (DUP). The onset of flooding significantly (p < 0.001) increased dissolved concentrations of all forms of P. The release of TDP coincided with a reduction in redox potential, suggesting reductive dissolution of P bearing iron/manganese (Fe/Mn) minerals as indicated by a significant positive correlation between TDP and dissolved Fe (r = 0.430, p < 0.001) and TDP and dissolved Mn (r = 0.622, p < 0.001). Flooding of the dried soils caused a significantly greater increase in the dissolved P concentrations of all forms of P relative to their moist‐flooded counterparts. This could be due to a combination of factors which are associated with soil drying and flooding. The Crediton dry‐flooded soils released higher concentrations of DRP upon flooding (e.g. 0.14 mg P L−1 on day 1 after flooding) perhaps due to its higher concentrations of water‐ and NaHCO3‐extractable P than the Hallsworth dry‐flooded (HDF) soil (0.03 mg P L−1 on day 1 after flooding). However, most of the P in the water column of the dry‐flooded soils was unreactive, with the HDF soil releasing higher concentrations of DUP, likely due to its higher organic matter and microbial biomass P contents. The results suggest that flooding of dried soils has greater potential to enhance mobilisation of soil‐P than flooding of moist soils and thus has potential implications for soil fertility and surface water quality. Highlights Flooding significantly increased dissolved concentrations of all forms of P. Dried soils released much greater P than their moist counterparts upon flooding. Increased amounts of P in the floodwater coincided with reductions in redox potential and biomass P. Soil with greater amount of biomass‐P and organic matter released greater amounts of dissolved unreactive P.